The Lecanora dispersa group (Lecanoraceae) in Argentina - de la Rosa, Iris Nadia (2011)
A preliminary study of the Lecanora dispersa group in Argentina is presented. Two species (L. dispersa and L. hagenii) have been previously recorded and their known distribution is extended, one species (L. semipallida) is a new record from Argentina, and five taxa (L. flowersiana, L. persimilis, L. torrida, L. wetmorei and L. zosterae var. zosterae) are reported for the first time from South America. Three species (L. albescens, L. crenulata and L. populicola) previously recorded for Argentina have not been confirmed as occurring in this country. Lecanora aff. fugiens is also treated and compared to the related species. The morphology, anatomy, secondary metabolites, distribution and ecology of the nine studied taxa are described and discussed, and a key to the taxa is included.